The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jmmm.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect and piezoresponse of engineered ferroelectric-ferromagnetic heterostructures

Abstract: Present study reports the magnetocaloric effect (MCE) and piezoresponse of integrated ferroelectric-ferromagnetic heterostructures of PbZr0.52Ti0.48O3 (PZT) (5 nm)/ Bi-Sr-Ca-Cu2-OX (BSCCO) (5 nm)/ La0.67Sr0.33MnO3 (LSMO) (40 nm)/ MgO. Magnetic and pizoresponse behavior of the heterostructures are found to be governed by magneto-electric coupling and induced lattice strains. In addition, the MCE is studied using Maxwell equations from both Field Cooled (FC) and Zero Field Cooled (ZFC) magnetization data. Maximu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Mechanical switching has been reported in a series of ferroelectric materials, such as BiFeO 3 , 17−19 BaTiO 3 , 10,20 (1 − x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (x = 0.32, 0.40), 21 (Zr 0.2 Ti 0.8 )O 3 , 22 PbZr 0.48 Ti 0.52 O 3 . 23 The flexoelectric effect on ferroelectric polarization was investigated by regulating the lattice mismatch with the substrates, 4 oxygen vacancy, 7,24,25 and deposition temperature 26 during the film growth and bending the substrate directly. 27 Many strategies have been conducted to decrease the threshold force of ferroelectric domain switching.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical switching has been reported in a series of ferroelectric materials, such as BiFeO 3 , 17−19 BaTiO 3 , 10,20 (1 − x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (x = 0.32, 0.40), 21 (Zr 0.2 Ti 0.8 )O 3 , 22 PbZr 0.48 Ti 0.52 O 3 . 23 The flexoelectric effect on ferroelectric polarization was investigated by regulating the lattice mismatch with the substrates, 4 oxygen vacancy, 7,24,25 and deposition temperature 26 during the film growth and bending the substrate directly. 27 Many strategies have been conducted to decrease the threshold force of ferroelectric domain switching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(a) The threshold force for mechanically induced single-domain inversion in several ferroelectric films reported to date. (b) Relationshipbetween threshold force and in-plane strain 10,19,23,28,29.…”
mentioning
confidence: 99%
“…Piezocomposites contain piezoelectric materials as the fibre phase and a passive material (epoxy) as the matrix phase. Piezocomposites are predominantly used in the actuator, vibration control, energy harvesting and cooling applications [2,[5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to low phase-transition temperature of ferromagnetic materials, extensive studies have been carried out for magnetocaloric effect with their applications in solid-state ferromagnetic refrigeration devices [14,18,19] as compared to electrocaloric effect (ECE). Though ferromagnetic materials can produce giant cooling effect near room temperature [20,21], it requires a strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[1 ] In a related attempt Edwards et al [6] reported the mechanical switching threshold (1000 nN: estimated tip pressure = 0.8 GPa; tip radius = 20 nm) of polycrystalline PbZr 0.53 Ti 0.47 O 3 , which lays at the morphotropic phase boundary (MPB) of the Pb(Zr x Ti (1−x) )O 3 family. Compositions close to the MPB of Pb(Zr x Ti (1−x) )O 3 offer the possibility of transitions between tetragonal and rhombohedral phases due to small strains [27][28][29][30][31] as well as the co-existence of tetragonal and rhombohedral phases, [5,32] and have been investigated with respect to thickness-dependent flexoelectric fields, [32] making them ideal for pressure-induced polarization switching. Therefore, in this work, we explore the ferroelectric and mechanical Figure 1a shows the room temperature (297 K) HR-X-ray diffraction (XRD) patterns of the PZT/YBCO/LAO heterostructures.…”
mentioning
confidence: 99%